1976
DOI: 10.1111/j.1365-2389.1976.tb02005.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Copper‐porphyrin Complexes in Soil Humic Acids

Abstract: Electron paramagnetic resonance (e.p.r.) spectroscopy has been used to show that humic acids, which were isolated from a range of soils and from which most of the iron was removed by boiling with hydrochloric acid, contain copper in the form of porphyrin complexes. The amounts of porphyrin-bound copper in the acid-boiled humic acids were estimated to be < 20 mg/kg (equivalent to o*og-o.g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…The observation that the strength of binding of Cu by humic acids decreases with an increase in the amount of Cu applied (43,55,56) is in agreement with other observations suggesting that Cu, when present in low amounts in peat soils, is so tightly complexed that it cannot be taken up by crop plants. Ennis and Brogan (49) prepared a Cu·humic acid complex by saturation with CuS0 4 and found that the Cu became increasingly unavailable to oat plants as more and more of the Cu was removed by chemical extraction (increasing concentrations of HCI were used).…”
Section: Aa------decrease In Exchange-acid1ty--------------~5oosupporting
confidence: 88%
“…The observation that the strength of binding of Cu by humic acids decreases with an increase in the amount of Cu applied (43,55,56) is in agreement with other observations suggesting that Cu, when present in low amounts in peat soils, is so tightly complexed that it cannot be taken up by crop plants. Ennis and Brogan (49) prepared a Cu·humic acid complex by saturation with CuS0 4 and found that the Cu became increasingly unavailable to oat plants as more and more of the Cu was removed by chemical extraction (increasing concentrations of HCI were used).…”
Section: Aa------decrease In Exchange-acid1ty--------------~5oosupporting
confidence: 88%
“…If Cu^"^ were established as the absorbed species, studies of the type presented would allow calculation of a value for external acu2+ at zero ApiQ^2+ which could be compared with acu2+ in the solution of copper deficient soils. Especially in organic soils where humic materials complex copper strongly (Goodman & Cheshire, 1976;Petruzzelh & Guidi, 1976), pCu^* in the soil solution can be expected to exceed values of 13 or 14.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is known to bind to salicylic and dicarboxylic type sites in humic materials { 5 ) as well as to nitrogen and sulfur containing groups (11,12). But it is the salicylic and dicarboxylic groups which are responsible for most of the binding (9,10).…”
Section: Discussionmentioning
confidence: 98%